2018
DOI: 10.21763/tjfmpc.399922
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Hizmet Uzmanlarının Mesleki Bağlılık Düzeylerinin Bazı Değişkenlere Göre İncelenmesi

Abstract: Objective: This study was conducted to examine work commitment of social workers up to some variables such as gender, age, income level, marital status, working time/duration etc. Method: Study was executed with 153 social workers via relational screening model. Personal information form and Professional Commitment Scale developed by Meyer, Allen and Smith (1993) were used in the study. Findings: Up to the research results; meaningful differences were found within the sub-dimension of professional commitment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Namely, students with low or high family income were more committed to profession than students with moderate family income. Similarly, Saruc et al ( 41 ) showed that the professional commitment level of social workers increased with the increase in income level.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Namely, students with low or high family income were more committed to profession than students with moderate family income. Similarly, Saruc et al ( 41 ) showed that the professional commitment level of social workers increased with the increase in income level.…”
Section: Discussionmentioning
confidence: 88%
“…Contrary to this, higher commitment levels among men were found among students ( 37 ), administrative staff of a state university ( 38 ), and nurses ( 39 ). In some studies, commitment level did not significantly differ between the sexes ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 95%